2007
DOI: 10.1111/j.1365-2966.2007.11736.x
|View full text |Cite
|
Sign up to set email alerts
|

Shock oscillation model for quasi-periodic oscillations in stellar mass and supermassive black holes

Abstract: We numerically examine centrifugally supported shock waves in 2D rotating accretion flows around a stellar mass (10 M⊙) and a supermassive (106 M⊙) black holes over a wide range of input accretion rates of . The resultant 2D shocks are unstable with time and the luminosities show quasi‐periodic oscillations (QPOs) with modulations of a factor of 2–3 and with periods of a tenth of a second to several hours, depending on the black hole masses. The shock oscillation model may explain the intermediate frequency QP… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 27 publications
3
43
0
Order By: Relevance
“…Our models are different from those of Okuda et al (2007). Whereas they considered axisymmetric oscillations, we investigate the nonaxisymmetric variety.…”
Section: Black Hole Qposmentioning
confidence: 99%
See 1 more Smart Citation
“…Our models are different from those of Okuda et al (2007). Whereas they considered axisymmetric oscillations, we investigate the nonaxisymmetric variety.…”
Section: Black Hole Qposmentioning
confidence: 99%
“…The shock oscillation model for black hole QPOs has been investigated by many authors ( Das et al 2003a( Das et al , 2003bChakrabarti et al 2004;Aoki et al 2004;Okuda et al 2007). Recently, for example, Okuda et al (2007) performed two-dimensional pseudo-Newtonian numerical simulations of the shock oscillation in the meridian section, assuming axisymmetry and taking into account the cooling and heating of gas and radiative transport. They demonstrated that a quasi-periodically oscillating shock wave forms around the black hole.…”
Section: Black Hole Qposmentioning
confidence: 99%
“…[33]- [17] and references therein. Numerical works have also been reported for such flow configurations in [58]- [53] and references therein.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies include hydrodynamic shocks (e.g., Nobuta & Hanawa 1994;Lu et al 1997;Chakrabarti 1990;Fukumura & Tsuruta 2004) and magnetohydrodynamic (MHD) shocks (e.g., Koide et al 1998Koide et al , 2000Das & Chakrabarti 2007;Takahashi et al 2002Takahashi et al , 2006Fukumura & Kazanas 2007b;Fukumura et al 2007, hereafter F07;Takahashi & Takahashi 2010). In particular, extensive theoretical studies of various types of shocks have been conducted to date in an attempt to understand their dynamical behavior; e.g., shock oscillation in the context of quasi-periodic oscillations and its spectroscopic signatures (e.g., Chakrabarti & Titarchuk 1995;Molteni et al 1996Molteni et al , 1999Acharya et al 2002;Okuda et al 2004Okuda et al , 2007Nagakura & Yamada 2008) that may be relevant for X-ray Binaries (XRBs), for example. Independent general relativistic (GR) MHD (GRMHD) simulations of the tilted accretion disk clearly show that the compression of the plunging plasma in the inner region (  r r 10 g ) leads to the formation of standing shocks (e.g., Fragile et al 2007;Fragile & Blaes 2008;Generozov et al 2014) depending on the characteristics of the disk geometry and the BH spin (e.g., Morales et al 2014).…”
Section: Introductionmentioning
confidence: 99%